2007
DOI: 10.2298/bah0701339r
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropic action of medication administered in various doses to synchronise the oestrus of anoestral sheep

Abstract: The experiment included 20 ewes of the Tsigai breed, allocated in two groups of 10 animals each. Inducing of oestrus synchronisation was performed during anoestral season (April-May) through vaginal sponges containing gestagens, and administration of Gravohormon (Vetbiopharm, Bulgaria)-500 UI in group 1 ewes and 1000 UI in group 2 ewes. Macromorphological study of the ovaries was carried out by means of laparoscopy after the adopted methods-on the 56 th hour, 72 nd hour and 5 th day following sponge withdrawal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(1 reference statement)
1
1
0
Order By: Relevance
“…Progesterone concentration started to increase 50 h after injection and at 122 h it already exceeded 0.5 ng/ml. Our results corresponded closely to the findings of Ralchev et al (2008) who studied the changes in plasma progesterone concentrations in Tsigai ewes injected with 500 and 1000 UI gonadotropin at the time of sponge removal during the non-breeding season. In both groups of sheep progesterone concentration began to increase 72 h after gonadotropin injection reaching the peak levels of 0.47 and 0.33 ng/ml, respectively, by the 5 th day posttreatment.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Progesterone concentration started to increase 50 h after injection and at 122 h it already exceeded 0.5 ng/ml. Our results corresponded closely to the findings of Ralchev et al (2008) who studied the changes in plasma progesterone concentrations in Tsigai ewes injected with 500 and 1000 UI gonadotropin at the time of sponge removal during the non-breeding season. In both groups of sheep progesterone concentration began to increase 72 h after gonadotropin injection reaching the peak levels of 0.47 and 0.33 ng/ml, respectively, by the 5 th day posttreatment.…”
Section: Resultssupporting
confidence: 90%
“…Ungerfeld et al (2002) recommended the application of progestagens in the form of vaginal sponges for a period of 6-14 days in combination with PMSG. It was found that gonadotropins stimulate follicular growth, increase the ovulation rate and fertility and improve synchronization (Cline et al, 2001;Maurel et al, 2003;Ralchev et al, 2008).…”
Section: Introductionmentioning
confidence: 99%